Mass plantlets regeneration from scalps of banana cv. tanduk (Musa spp. AAB group) - Elhory S. M. A. (Malaysian Society of Plant Physiology, 2019)
An experiment was conducted to determine the best concentration of BAP combined with 1.0 ɰM lAA to induce scalp formation from shoot tips of Musa spp. cv. Tanduk. The BAP concentrations assessed were 0.0, 10.0, 50.0 and 100.0 µM. BAP at 100.0 µM combined with 1.0 ɰM lAA induced prolific scalp formation after 4-7 subcultures, while BAP at 50.0 µM or less resulted only in shoot formation. Plantlet regeneration from the scalps were assessed using different BAP concentrations of 1.0, 2.5 and 5.0 µM. The highest number of shoot proliferation occurred on 2.5 µM BAP with an average of 40.6 shoots after two sub-cultures. The shoots were rooted on half and full strength MS media without growth regulator, as well as on full strength MS medium with 1.0, 5.0 and 10.0 µM IBA. The highest number of roots produced per shoot was obtained on full strength MS medium containing 10.0 µM IBA.